بنية النص الروائي النسوي رواية بيروت 75 لغادة السمان أنموذجا - رزيق, ميسة, عفاف حياة (Univercty of Eloued, 2020)
This note discusses the structure of the feminist narrative text in Ghada Al-Samman's novel Beirut 75. It aims to uncover the narrative components and their interaction between them by delving into them further. In order to obtain knowledge regarding this topic, we formulated the following problem: While the narrative structure was represented in Ghada Al-Samman's Beirut 75 novel, and how did the novelist draw its levels within the narrative text, which includes a set of questions? The historical curriculum was present to follow the emergence of the Syrian feminist novel and the structural approach that examines its narrative components. As for structuring the research, we divided it into two chapters: A theoretical chapter that organizes the emergence of the Syrian feminist novel, its trends, and its issues. In my last application, we dealt with the structure of the character in the novel, which turned out to be based on the internal and external dialogues of the characters, which contributed to providing an interpretive opportunity for the reader, and the abundance of characters gives movement, diversification, and organization that leads to the clarification of the role of each character and the significance they achieve. As for the structures of time and place; In the novel there is a clear focus on them; This appears first in the chronological paradoxes of anticipating the presentation of events prematurely and retrospectively of past events; And relying on the rhythm of time to speed up and slow down events through pause, deletion and scene; In addition to embodying the chronological frequency of all kinds. Then the spatial space, as the novel has open and closed spaces that take on a sign that reflects its general significance and the textual space that shows the novel in a formal and artistic way. In the end, we can say that Ghada El-Samman's Beirut 75 novel is a symbolic novel with a tragic and mysterious character that talks about the nature of life in Beirut and conveys the reality to us through political and social conflict and reflects the harbingers of the Lebanese civil war.
Keywords: بنية النص – النص الروائي النسوي – الرواية النسوية; Text structure - Feminist narrative text - Feminist narration